Aerodynamic optimisation of civil aero-engine nacelles by dimensionality reduction and multi-fidelity techniques - Tejero, Fernando; MacManus, David G.; Hueso Rebassa, Josep; Sánchez-Moreno, Francisco; Goulos, Ioannis; Sheaf, Christopher T. (Emerald, 2022)
Purpose - Aerodynamic shape optimisation is complex due to the high dimensionality of the problem, the associated non-linearity and its large computational cost. These three aspects have an impact on the overall time of the design process. To overcome these challenges, this paper develops a method for transonic aerodynamic design with dimensionality reduction and multi-fidelity techniques. Design/methodology/approach - The developed methodology is used for the optimisation of an installed civil ultra-high bypass ratio aero-engine nacelle. As such, the effects of airframe-engine integration are considered during the optimisation routine. The active subspace method is applied to reduce the dimensionality of the problem from 32 to 2 design variables with a database compiled with Euler CFD calculations. In the reduced dimensional space, a co-Kriging model is built to combine Euler lower-fidelity and RANS higher-fidelity CFD evaluations. Findings - Relative to a baseline aero-engine nacelle derived from an isolated optimisation process, the proposed method yielded a non-axisymmetric nacelle configuration with an increment in net vehicle force of 0.65% of the nominal standard net thrust. Originality - This work investigates the viability of CFD optimisation through a combination of dimensionality reduction and multi-fidelity method, and demonstrates that the developed methodology enables the optimisation of complex aerodynamic problems.
Keywords: Optimization; dimensionality reduction; multi-fidelity; active subspace; co-kriging